Young and Old Sugar Apple (Annona squamosa Linn) Leaf Extracts As an Aedes aegypti Larva Insecticide - Abdul Khair; Noraida Noraida (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2019)
Vector-borne diseases are still a health problem in some tropical countries. One vector-borne disease is Dengue Hemorrhagic Fever (DHF). DHF never decreases and even tends to continue to increase, and many cause deaths in children, 90% of them attack children under 15 years. DHF cases in 2018 amounted to 65,602 cases, with 467 deaths (CFR = 0.71%). The behavior of holding water in various places such as tubs and tendons indirectly creates a breeding place for Aedes aegypti mosquitoes. The use of chemicals as insecticides can cause the death of non-target animals, environmental pollution, and the occurrence of vector resistance to insecticides. Therefore it is necessary to do other methods including the use of vegetable insecticides. Sugar apple leaves can be used to kill Aedes aegypti larvae. Sugar apple leaves will obtain throughout the year. The purpose of this study is to know the ability of young and old sugar apple leaves to kill Aedes aegypti larvae. This type of research is a posttest only control group design. The study sample was part of the Aedes aegypti larvae on the final instar III. The experiment to kill Aedes aegypti larvae use two types of sugar apple leaf extract, namely young and old sugar apple leaves with nine treatments four replications. Each treatment consisted of 25 larvae. The research results show There was no significant difference in the number of dead larvae using either extracts from young sugar apple leaves or old sugar apple leaves. LC90 of sugar apple leaf extract was between 0.05632 to 0.08324% and the effective residual age at LC90 (0.06568%) with the death of Aedes aegypti larvae was 92% over 24 hours (1 day).